2019
DOI: 10.1007/s12149-019-01355-8
|View full text |Cite
|
Sign up to set email alerts
|

Overall survival and progression-free survival in patients with primary brain tumors after treatment: is the outcome of [18F] FDOPA PET a prognostic factor in these patients?

Abstract: Aim To investigate the progression-free survival (PFS) and the overall survival (OS) in a population affected by primary brain tumors (PBT) evaluated by [ 18 F]-l-dihydroxyphenylalanine ([ 18 F] FDOPA) positron emission tomography/computed tomography (PET/CT). Materials and methods 133 subjects with PBT (65 women and 68 men, mean age 45 ± 10 years old) underwent 18 F FDOPA PET/CT after treatment. Of them, 68 (51.2%) were Grade II, 34 (25.5%) were Grade III and 31 (23.3%) were Grade IV. PET/CT was scored as pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 24 publications
(36 reference statements)
0
16
0
Order By: Relevance
“…starting from the slice with the highest uptake of the radiopharmaceutical. Moreover, the use of co-registered MRI images [ 16 ] permitted a correct placement of the VOI, even in tumors with involvement of the striatum ( Figure 1 A). From the VOI, the maximum standardized uptake value for the site of recurrence (SUVmax lesion) was calculated on a dedicated workstation (version 4.4, Advantage Workstation, GE Healthcare, Chicago, IL, USA).…”
Section: Methodsmentioning
confidence: 99%
“…starting from the slice with the highest uptake of the radiopharmaceutical. Moreover, the use of co-registered MRI images [ 16 ] permitted a correct placement of the VOI, even in tumors with involvement of the striatum ( Figure 1 A). From the VOI, the maximum standardized uptake value for the site of recurrence (SUVmax lesion) was calculated on a dedicated workstation (version 4.4, Advantage Workstation, GE Healthcare, Chicago, IL, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, a recent study reported results that are more restrained. Chiaravalloti et al retrospectively included 133 primary brain tumors [62]. They correlated the OS and the PFS with the SUV max and the SUVr (defined by the SUV max of the tumor divided by the SUV max of the contralateral occipital region).…”
Section: Prognostic Valuementioning
confidence: 99%
“…The use of PET as a prognostic tool for high-grade gliomas has been investigated over a period of several years. A previous study conducted on [ 18 F] dihdryoxyphenylalanine ([ 18 F] FDOPA) within a large target population did not find that the amino acid PET tracer had any prognostic power (19). However, studies on [ 18 F] FET have shown that this tracer could have prognostic potential (12, 13).…”
Section: Discussionmentioning
confidence: 99%